Surgical reconstructive procedures of the chest wall after mediastinitis Plastische Rekonstruktionsverfahren der Brustwand nach Mediastinitis - Ried, M.; Geis, S.; Potzger, T.; Neu, R.; Klein, S.; Prantl, L.; Hofmann, H. S.; Dolderer, J. H. (Chirurg, 2016)
Sternal osteomyelitis as a direct consequence of advanced mediastinitis or as in most cases after median sternotomy is still associated with a prolonged hospital stay, increased morbidity and postoperative mortality. Early diagnosis and an adequate surgical treatment are decisive for the prognosis. Prerequisites for a secondary stabilization of the chest wall using wires or plates are sterile wound conditions. Diverse reconstructive techniques are available for anterior chest wall reconstruction depending on the defect size and localization. The various reconstructive methods including local and free flap coverage are described in this review article.
CRIS-Team Scopus Importer:2024-12-11
Keywords: Chest wall; Omentum; Osteomyelitis; Sternum; Surgical flaps